What is the Impact of Social Media Advertising Content on Alpha Generation's Financial Understanding? - Reni Nur Arifah; Yetty Yuliany K (Institut Karya Mulia Bangsa, 2025)
Generation Alpha (2011-2025) is known as the generation that is very close to digital technology and is considered the most intelligent generation compared to previous generations. Every week around 2.5 million children of this generation are born worldwide. They are growing up as the most internet- connected generation in history. According to McCrindle, Generation Alpha is highly gadget-dependent, less social, less creative and more individualistic. They want everything fast and instant, and have little respect for process. Their interest in gadgets leads to social alienation. This study examines the impact, experiences and perceptions of the alpha generation on advertising content on social media on teenagers in Nyamat Village by linking knowledge about financial literacy. Social media advertising has a growing influence on the Alpha Generation. Ads targeted at them often employ strategies that capitalize on current trends, digital celebrities and short-form attention-grabbing content. However, how Generation Alpha responds to and perceives this advertising content is still a relevant question to research, especially in rural areas such as Nyamat Village. Data from interviews conducted in Nyamat Village with 12 informant using the narrative descriptive analysis method. The results showed that almost all of these alpha gen teenagers use tiktok and instragram social media which they often see every day and they are interested in buying it so they have to save up first and will eventually ask their parents for money